CONCORD DALAM BAHASA ARAB DAN BAHASA INGGRIS: SEBUAH KAJIAN KONTRASTIF - , AGUS SALIM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis is a contrastive research on concord in Arabic and English. The aim of this research is to explain typology of the two languages in the forms of their concord and to describe similarity and difference of the concord forms of the two languages. The Method used in this research is descriptive qualitative method. There are two methods used for analyzing data in this research, namely distributive method and comparative method. In the distributive method, the technique used is basic technique of direct element division. Besides that, it is also used following technique covering mark reading technique, substitutive technique, deletion technique, reversing technique, and marking technique. In the comparative method, the technique used is comparative relation technique. From the result of the research, it is concluded that generally, the concept of concord in level of clause in Arabic language involves grammatical categories of person, gender, and number. The grammatical categories are points of concordance in concord between subject and predicate in Arabic clauses. In English language, generally the concept of concord in level of clause only involves grammatical categories of person and number. The grammatical categories are points of concordance in concord between subject and predicate in English clauses. From the result of the research, it is concluded that in Arabic language it is discovered of three shapes of concords in level of clause, namely: concord of subject â predicate in verbal clause of mÄdhÄ«, concord of subject â predicate in verbal clause of mudhÄriâ, and concord of subject â predicate in nominal clause. In English language, it is discovered of five shapes of concords in level of clause, namely: concord of subject â predicate in simple present tense, concord of subject â predicate in present continuous tense, concord of subject â predicate in present perfect tense, concord of subject â predicate in simple past tense, and concord of subject â predicate in past continuous tense. From the result of the research, it is concluded that generally the concept of concord in level of phrase in Arabic language involves grammatical categories of gender, number, definiteness, and case mark. The grammatical categories are points of concordance in concord between elements that form phrase in Arabic language. In English language, generally the concept of concord in level of phrase only involves grammatical categories of number. The grammatical categories are points of concordance in concord between elements that form phrase in English language. From the result of the research, it is concluded that in Arabic language it is discovered of three shapes of concord in level of phrase, namely: concord between demonstrative pronoun and noun, concord between noun and adjectival noun, and concord between numeral and noun. In English language, it is also discovered of three shapes of concord in level of phrase, namely: concord between demonstrative pronoun and noun, concord between determiner and noun, and concord between numeral and noun.